Isolation Bacteria from the Soil Rhizosphere Robusta Coffee Plant (coffea canephora l.) as an Producer Antibacteria: Isolation Bacteria from the Soil Rhizosphere Robusta Coffee Plant (coffea canephora l.) as an Producer Antibacteria - Hardi, Samsu; Pratama, Agus sangka; Hasanuddin, Rusman (Program Studi Farmasi, Universitas Islam Makassar, 2023)
Rhizosphere soil is the soil around plants that has the same content as the plant where it grows. Much of the Rhizosphere soil content can be used as an antibacterial. The purpose of this study was to isolate bacteria from the rhizosphere soil of robusta coffee plants (Coffea canephora L.) as antibacterial. This research method begins with the isolation of rhizosphere bacteria, purification, antibacterial activity screening test, fermentation antibacterial activity test and thin layer chromatography. The results obtained were in the isolation process, 4 isolates were obtained. Isolate 4 had the greatest activity against Escherhicia coli bacteria, so the next step was used with a concentration of 2.5%; 5%; 10% which have inhibition diameters of 6.23mm, 6.29mm and 6.40mm. The results for the identification of thin layer chromatography of the ethyl acetate extract showed no spots (no compound). Based on these data, it can be concluded that a concentration of 10% has the largest inhibitory diameter against Escherhicia coli bacteria, which is 6.40mm but cannot be identified by the TLC method.